Computer Networks A Systems Approach - Peterson, Larry L. (Elsevier Science, 2007)
Computer Networks, 4E is the only introductory computer networking book written by authors who have had first-hand experience with many of the protocols discussed in the book, who have actually designed some of them as well, and who are still actively designing the computer networks today. This newly revised edition continues to provide an enduring, practical understanding of networks and their building blocks through rich, example-based instruction. The authors' focus is on the why of network design, not just the specifications comprising today's systems but how key technologies and protocols actually work in the real world to solve specific problems. The new edition makes less use of computer code to explain protocols than earlier editions. Moreover, this new edition shifts the focus somewhat higher in the protocol stack where there is generally more innovative and exciting work going on at the application and session layers than at the link and physical layers. * Completely updated with new sidebar discussions that cover the deployment status of protocols described in the book. * Addition of sizeable number of new exercises and solutions. * Downloadable Opnet network simulation software and lab experiments manual. * New and revised instructor support material, including Powerpoint slides, eps version of figures appearing in the text; sample exams; lecture notes; UNIX sockets programming assignments
Description based on publisher supplied metadata and other sources
Keywords: Computer networks; Rechnernetz; Lehrbuch